Peningkatan Hasil Belajar Matematika melalui Penerapan Model Pembelajaran Discovery Learning Berbantuan LKPD - Nila Sari Latif (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2019)
This study aims to identify the improvement in mathematics learning achievement for students of grade VIII A at SMPN 9 Marusu by applying discovery learning models using LKPD. Subjects of this study were 26 students of grade VIII A SMPN 9 Marusu academic year of 2018/2019. This study is a classroom action research conducted in two cycles in which consisting of several stages, namely planning, implementation, observation and evaluation as well as reflection. Data collection method applied were students’ learning achievement test conducted at the end of each cycle, observation, reflection, documentation and student responses. The collected data were analyzed using quantitative and qualitative method. The achievement achieved after the discovery learning models using LKPD was applied are: (1) in cycle I, the average score of mathematics learning achievement of students is 61.92 increasing to 75.38 in cycle II. The deviation standard in the first cycle is 12.66 and increasing to 9.48 in the second cycle of the ideal score 100, (2) There is an increase in the frequency of student activities and student attitudes. Based on the above research achievement, it can be concluded that there is an increase in mathematics learning achievement for students of grade VIII A at SMPN 9 Marusu by applying discovery learning models using LKPD.